Sistem Pengendali Robot Pembersih Lantai Dengan Perintah Suara Berbasis Android - Dalimunthe, Ruri Ashari; Sena, Maulana Dwi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
To clean the floor, it can be done manually by using a floor mop along with floor cleaning fluid, but this will result in a floor that is already clean. Still, the implementation time is long enough to interfere with the time of mothers who are office workers or manufacturers to help their husband's income. . In the process of cleaning the floor, cleaning the floor can be done until the floor is clean so that the children are comfortable playing on the floor. The process of cleaning floors can be done in various ways, either manually or automatically. To clean the floor with a large floor size more quickly, the floor is cleaned with machine power. But the range and limitations of floor cleaning machines exist. So it is necessary to make a robot that works automatically without human assistance to do the cleaning so that the job is done quickly and the area limit of the cleaning results is greater. The system will work using penggerak technology remotely using Bluetooth. This system aims to connect communication between wheeled robots and smartphones via Bluetooth communication media. From the test results, the author has successfully applied Bluetooth technology to a wheeled robot by providing instructions such as forward, backward, turn right, turn left, and stop. This robot is used to clean floors quickly and practically so that it can be done by itself.